EXPLORING THE EXPERIENCE OF MARITAL SATISFACTION AMONG CHINESE COUPLES IN HONG KONG WHO HAVE TWO YOUNG CHILDREN - Shuk Ha Lam (PEOPLE: International Journal of Social Sciences, 2026)
This qualitative study explored the experience of marital satisfaction among Chinese couples in Hong Kong who have two young children through in-depth interview. The study examined three key aspects: change the marital relationship after having two children, strengthen the marital intimacy with traditional culture and connections to family support services with conceptual framework in family system theory, role theory and cultural dimensions theory. The qualitative study interviewed a total of 3 couples, which including three husbands and three wives. Findings revealed sixteen themes across seven categories. The study highlighted how marital satisfaction is affected by the factors related to parenting and childcare responsibilities. The key discoveries included the critical incidents, the parenting approaches for families with two children, maintaining marital intimacy, marital communication and the extended family support network within Chinese cultural contexts. The most significant finding of the study is that father’s involvement in family can strengthen marital relationships, contradicting previous research suggesting that having multiple children inevitably increases family stress and weakens the spousal bond. The study showed that the couples maintained marital intimacy through effective communication patterns, regular couple and family activities and adjusted expectations among spouses to achieve a well-balanced marital relationship. Furthermore, shared responsibility in childcare emerged as a key finding for enhancing marital satisfaction. Another significant finding was the important role of extended family support networks, especially grandparents. They provided crucial support to help couples with two children adapt within the Chinese cultural context in Hong Kong. This specific cultural support can enhance marital satisfaction indirectly. The study contributes to understanding the resilience of families with two young children and the foundation of common expectations in marital relationships. Based on the same values and commitments, couples demonstrated greater ability to adapt to the challenges of marriage and family life.